Linguistic Database for Translating Auxiliary Verbs from Uzbek into English - Qodirova Madinabonu Murodjon qizi (International Journal Of Literature And Languages, 2025)
This article analyzes linguistic issues encountered in the translation of Uzbek auxiliary verbs into English. In the Uzbek language, auxiliary verbs are used to express various grammatical meanings, including the continuity or completion of an action, the manner of execution, and the speaker’s attitude. In English, these meanings are conveyed through different grammatical constructions and independent verbs. Within the scope of this study, approximately 29 auxiliary verbs were identified to express around 70 grammatical meanings. The article examines their translation features and discusses the key methods for translating auxiliary verbs and the challenges in constructing a linguistic database.